Morphologische Verbfehler in elizitierten Narrativen bei russisch-deutsch bilingualen Kindern im Grundschulalter - Vorobyeva, Olga (ZAS Papers in Linguistics, 2019)
This paper focuses on morphological verb errors in elicited narratives of Russian-German primary school bilinguals. The data was collected from 37 children who were separated into four groups according to the age and language acquisition type (simultaneous and successive). The Multilingual Assessment Instrument for Narratives (MAIN) (Gagarina et al. 2012) was used for data collection. The narratives produced in mode telling after listening to a model story were analysed and morphological verb errors in Russian and German were classified. Therefore, the error classification of Gagarina (2008) for Russian monolingual children was expanded and for the classification of German errors an own classification was suggested. Errors in Russian typically produced by monolinguals and unique bilingual errors as well were documented. The results show that the language of the environment (German) increases with age. Older children make fewer errors than younger ones. Nevertheless, a strong heterogeneity between children within each group can be observed.